PENYELESAIAN SENGKETA PEMBAGIAN WARIS PADA MASYARAKAT ADAT DI DESA HAREFANAESE KABUPATEN NIAS UTARA - Dina Saputri; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Customary inheritance is part of customary law relating to norms or rules in determining the amountof assets, both material and immaterial that can be handed over to their descendants and also regulateswhen, how and how the process of transferring assets, both material and immaterial. Nias is a followerof Patrilineal culture, where the position of the father (male) has the main position in the lineage.Generally, in the customs of the Patrilineal community, the person who can inherit the inheritance isthe person who continues the lineage. The implementation of inheritance distribution to the indigenouspeople of Nias in Harefanaese Village experienced a shift from the customary rules that should be,where currently there are several families who have given inheritance to their daughters even though itis in the form of small items but there are also those who have given inheritance in the form of land.Even though there are customary provisions that regulate inheritance issues, there are stillproblems/conflicts that occur due to the implementation of inheritance distribution. The objectives ofthis study are as follows: First, to determine the implementation of inheritance distribution toindigenous peoples in Harefanaese Village, North Nias Regency, Second, to determine the settlement ofinheritance distribution disputes among indigenous peoples in Harefanaese Village, North NiasRegency. This research is a sociological law research. That is, this research directly observes thespaciousness, the research location is Harefanaese Village, North Nias Regency. The samplingtechnique is a purposive sampling technique. The research data collection uses primary data andsecondary data. The data collection technique in this study is interviews and literature review and isconcluded by qualitative. Can be drawn; first, that the implementation of the distribution that took placein Harefanaese Village, experienced many shifts from the customary rules that should have been, wherecurrently there are several families who have given inheritance to their daughters, secondly, thesettlement of inheritance distribution disputes to indigenous peoples in Harefanaese Village, North NiasRegency, namely by holding consultations.Keywords: Inheritance-Customary-Dispute Resolution